Segmental Meniscus Allograft Transplantation - Seiter, Max N. (Arthrosc Tech, 2021)
Meniscal tears treated with partial meniscectomies have been shown to significantly increase contract pressures within the tibiofemoral joint, and a complete focal meniscal deficiency may render the entirety of the meniscus functionally incompetent. Although various techniques of meniscal transplantation have been described, these techniques may require the excision of a considerable amount of healthy meniscal tissue. Furthermore, failures continue to frequently occur. Therefore, attempts to restoring normal knee kinematics and biomechanical forces are essential. Segmental meniscus allograft transplantations may offer the advantage of a robust repair by both maintaining knee biomechanics and biology while maximizing preservation of native meniscal tissue. Also, most meniscal deficiency involves only a portion of the meniscus, and thus we developed this technique to segmentally transplant only the deficient portion. The purpose of this Technical Note is to describe a technique of segmental medial meniscus allograft transplantation in a patient with focal medial meniscus deficiency.